Possible Protective Effect of Sertraline against Cisplatin-Induced Ototoxicity: An Experimental Study - Murat Ozturk; Selcuk Ucar; Fatih Sarı; Selvet Erdogan; Murat Topdag; Mete Iseri (The Scientific World Journal)
Background/Objective. Cisplatin is a widely used chemotherapeutic agent, but its ototoxicity side effect can occur in the majority of patients. Lots of agents were tried to prevent this, but there is not a routine treatment modality yet. The aim of this study was to evaluate the otoprotective effect of sertraline, which is an antidepressant with neuroprotective effects, against cisplatin, in rats. Design. Experimental animal study. Material and Methods. Forty-eight rats were randomly separated in two groups as groups I and II. Group I was identified as the control group and only a single dose of intraperitoneal cisplatin was administered. In group II, in addition to cisplatin, sertraline was administered to the rats through an oral cannula for ten-day period. Distortion product otoacoustic emission measurements were performed at the first day and the 10th day. Results. When the ototoxicity rates after cisplatin in group I and group II in distortion product otoacoustic emission measurements were compared, it was statistically significantly lower in group II in frequencies of 5652, 6165, 6726, 7336, and 7996 Hz (). Conclusion. Sertraline seems to have a protective effect on cisplatin ototoxicity and could be used to prevent the ototoxicity and also to treat the depression that occurred in cancer patients together.